2014
DOI: 10.1111/trf.12655
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity in cord blood units: occurrence and levels of antibiotics

Abstract: Approximately one-third of CB products contain significant amounts of plasma with residual antibiotics, which can affect the survival and growth of bacterial contaminants when performing the sterility test and potentially lead to false-negative results. Additional work is required to better understand whether residual antibiotics in CB affect penicillin-allergic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 26 publications
(37 reference statements)
0
13
0
Order By: Relevance
“…In an article published in TRANSFUSION , Akel and colleagues estimated that more than 30% of CB products collected in the United States contain residual antibiotics. Cayer and coworkers also reported the presence of inhibitory substances in 20 of 60 (33%) tested CB plasmas . Herein, we have found that bacterial growth inhibitors present in CB appear to significantly affect microbial survival and detection.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…In an article published in TRANSFUSION , Akel and colleagues estimated that more than 30% of CB products collected in the United States contain residual antibiotics. Cayer and coworkers also reported the presence of inhibitory substances in 20 of 60 (33%) tested CB plasmas . Herein, we have found that bacterial growth inhibitors present in CB appear to significantly affect microbial survival and detection.…”
Section: Discussionmentioning
confidence: 50%
“…[21][22][23] The potential influence of antimicrobials in samples used for CB microbial testing has been observed. 7,24 These substances might influence sterility testing, because they affect the survival of contaminating bacteria in tested samples, leading to false-negative results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the validation of this process, lack of bacterial growth was noticed for certain species and an internal investigation revealed this was due to the fact that the donors were under antibiotic treatment at the time of CB collection. It has been reported that approximately 33% of CB donated in Canada is obtained during cesarean section deliveries, with donors undergoing prophylactic antibiotic therapy . The most commonly used antibiotics include β‐lactams such as penicillin and aminoglycosides such as gentamicin .…”
mentioning
confidence: 99%
“…It has been reported that approximately 33% of CB donated in Canada is obtained during cesarean section deliveries, with donors undergoing prophylactic antibiotic therapy . The most commonly used antibiotics include β‐lactams such as penicillin and aminoglycosides such as gentamicin . ‐ Neutralization of antimicrobials in CB units is recommended for an optimal sterility testing process, a practice followed by several CB banks, including CB banks at Héma‐Québec and Australia, and the St Louis Cord Blood Bank & Cellular Therapy Laboratory .…”
mentioning
confidence: 99%